Adding Consolidation Capecitabine to Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer: A Propensity-Matched Comparative Study - Fang, Yifang; Sheng, Chengmin; Ding, Feng; Zhao, Weijie; Guan, Guoxian; Liu, Xing (Frontiers in Surgery, 2022)
Aim To determine whether adding consolidation capecitabine chemotherapy without lengthening the waiting period influences pathological complete response (pCR) and short-term outcome of locally advanced rectal cancer (LARC) receiving neoadjuvant chemoradiotherapy (NCRT). Method Totally 545 LARC who recieved NCRT and radical resection between 2010 and 2018 were enrolled. Short-term outcome and pCR rate were compared between patients with and without additional consolidation capecitabine. Logistic analysis was performed to identify predictors of pCR. Results After propensity score matching, 229 patients were matched in both NCRT and NCRT-Cape groups. Postoperative morbidity was comparable between groups except for operation time, which is lower in the NCRT group (213.2±67.4 vs 227.9±70.5, p = 0.025). Two groups achieved similar pCR rates (21.8% vs. 22.7%, p = 1.000). Tumor size (OR = 0.439, p < 0.001), time interval between NCRT and surgery (OR = 1.241, p = 0.003), and post-NCRT CEA (OR = 0.880, p = 0.008) were significantly correlated with pCR in LARC patients. A predictive nomogram was constructed with a C-index of 0.787 and 0.741 on internal and external validation. Conclusion Adding consolidation capecitabine chemotherapy without lengthening CRT-to-surgery interval in LARC patients after NCRT does not seem to impact pCR or short-term outcome. A predictive nomogram for pCR was successfully, and it could support treatment decision-making.